Medical teamwork and the evolution of safety science: a critical review - Neuhaus, Christopher; Lutnæs, Dag Erik; Bergström, Johan (Cognition, technology & work, 2020)
There is widespread consensus that teamwork constitutes one of the key requirements in today’s multidisciplinary and highly complex system of delivering care. In recent years, increasing attention has been given to questions of how to define, teach, measure, and improve teamwork in healthcare. However, one cannot help but feel a certain disconnect between this ongoing trend in healthcare with an associated bias towards judgemental and normative language, and contemporary thinking in safety science that explores concepts from complexity thinking, such as emergence and resilience. The aim of this critical review is to contrast prevailing approaches to teamwork in healthcare with current concepts in safety science.